Decreasing Numbers of Blood Cultures: Does it Matter?. (4th October 2017) - Rand, Kenneth; Beal, Stacy; Payton, Thomas; Allen, Brandon; Rivera, Kimberly
Abstract: Background: Between Jan 2014 and Dec 2016, there was a 22.4% decline in the number of blood cultures (BC) s received in the UF Health Shands Hospital microbiology laboratory, and a 39.4% decrease from the Emergency Department (ED) over the same period. Methods: We studied 34, 618 admissions from the ED between July 1, 2011 and December 31, 2016 who had a blood culture done within 48 hours of ED entry. Based on hospital discharge coding, 8, 617 had sepsis present on admission (POA) and 26, 001 were never septic. The time from ED admission to obtain a BC and the time to first intravenous (IV) antibiotic dose were analyzed by 6 or 12 h intervals up to 48 hours. Outcome measures were mean hospital and ICU length of stay days (HLOS) and ICU LOS respectively. Results: For non-septic (but not for septic patients) both HLOS and ICULOS were strongly correlated with the time of BC draw. HLOS rose from 5.1d if the culture was obtained within 0–12 hours to 7.46 days if delayed to 36–48 hours ( r = 0.982, P < 0.005) and ICU LOS rose from 0.67 days to 2.54 days over the same time ( r = 0.987, P < 0.005). Since the time to antibiotics could explain this effect, we looked at 12 h intervals of antibiotic administration. For septic patients, the HLOS rose from 10.9d to18.6d (P < 0.001) and ICULOS rose from 3.5d to 9.5d if antibiotics were given at 0–12h vs. 36–48h, (P < 0.001). For non-septic patients, the HLOS rose from 6.0d to 9.7d (P < 0.001) and ICULOS rose from 0.94d to 3.3d, (P < 0.001). To assess the role of getting a BC, we studied the effect of getting a blood culture over 48h within each 12h interval of antibiotic administration. Obtaining a BC in the first 12h was significantly associated both shorter HLOS and ICULOS for non-septic patients, but not for septic patients. For antibiotics given in 0–12h, HLOS was 5.46 d vs. 6.77 if BC was done in 0 -12h vs. 36 – 48h, ICULOS was 0.68d vs. 1.44d for 0–12h and 36–48h respectively (t-test P < 0.001 for both) and in-hospital mortality was 1.99% if BC was obtained within 12h vs. 2.97% after that time, P = 0.0091. Conclusion: Delay in administration of IV antibiotics for ED admissions strongly increases HLOS and ICULOS for both septic and non-septic patients. Delay in drawing a BC has an independent effect for non-septic patients that correlated with longer HLOS, ICULOS and higher mortality. Disclosures: All authors: No reported disclosures.